First love eaudiobook - Patterson, James (2014)
In this New York Times bestseller, two high school students leave their hometown on the West Coast to go on an impulsive cross-country road trip in this moving romance about friendship and the power of love. Axi Moore is a "good girl": She studies hard, stays out of the spotlight, and doesn't tell anyone that she wants to run away from it all. The only person she can tell is her best friend, Robinson-and she's madly in love with him. When Axi impulsively invites Robinson to come with her on an unplanned cross-country road trip, she breaks the rules for the first time in her life. But the adventure quickly turns from carefree to out-of-control . . .